Effect of Varying Doses of Estradiol Benzoate on the body weight and blood picture in Turkeys: Saad J. Gatie, Bassam A. Al-Shimmary and Mohammed S. Almuslehi - A. Al-Shimmary, Saad J. Gatie, Bassam (The Iraqi Journal of Veterinary Medicine, 2012)
A present study was carried out to investigate the effects of Estradiol benzoate 2 (mg/ml) hormone doses on the body weight and blood picture of Turkeys birds through studying the following parameters: body weight, RBC count , total WBC, MCV, MCH, MCHC, and platelet PLT. Forty growing Turkeys (30 days age) weighting between (250-350)gm were randomly divided into four groups (ten each group) treated as follows: Turkeys in the first group were injected with single dose of Estradiol benzoate (1 mg) on the first day of experiment (30 day post hatching) subcutaneously in the neck and termed as G1 group, the Turkeys in the 2nd group (G2) were injected Estradiol benzoate (2 mg) on the first day of experiment subcutaneously in the neck while the Turkeys in the third group (G3) were injected Estradiol benzoate (0.3 ml) at the first day of experiment subcutaneously in the neck the fourth group (G4) served as control, body weight was determined on (0, 15 and 30) days of experiment and blood samples were collected on 15th and 30th day of the experiment from groups to evaluate the blood parameters. Results revealed a significant increase (P<0.05) in body weight of G1, G2 and G3 in a comparison with control group at (15 and 30) days of experiment. Furthermore, in comparison among treated groups G2 and G3 also showed a significant increase (P<0.05) in the body weight as compared with G1 group during periods. Moreover, data revealed that all treated groups showed non-significant differences in blood parameters experiment as compared with control group.